How Did The Financial Markets Respond to The COVID-19 Pandemic? Empirical Evidence from BRICS Countries - Kavita Chavali; Hazem Al Samman; Syed Jamil (Faculty of Economic and Business, 2021)
The paper aims to evaluate the reaction of stock markets in BRICS countries (Brazil, Russia, India, China, and South Africa) to the outbreak of the COVID-19 pandemic. The study uses ARCH and GARCH models that use daily stock prices from January 1, 2020, to September 2, 2020. The financial market response was analyzed in two phases. The first phase analyses the financial markets' response within 30 to 60 days from the first day of confirmed cases of COVID-19. The second phase analyses the financial market response post 30 to 60 days of initial confirmed cases. The study results conclude that the share prices decreased, but in the second phase, the markets responded positively. Our results conclude that governmental support played an important role in mitigating the repercussions of the COVID-19 outbreak on stock markets in BRICS countries.JEL Classification: E44, G15, G10How to Cite:Chavali, K., Al Samman, H., & Jamil, S. A. (2021). How Did The Financial Markets Respond to The Covid-19 Pandemic? Empirical Evidence from BRICS Countries. Etikonomi, 20(2), xx– xx. https://doi.org/10.15408/etk.v20i2.20339.